Antioxidant Activity of Surinamese Medicinal Plants with Adaptogenic Properties and Correlation with Total Phenolic Contents - R.A. Mans, Dennis; Friperson, Priscilla; Pawirodihardjo, Jennifer; Djotaroeno, Meryll (Journal of Antioxidant Activity, 2020)
Plant-based preparations are commonly used in Suriname (South America) as adaptogens. In this study, fifteen alleged adaptogenic Surinamese plants have been assessed for their antioxidant activity (AA), total phenolic contents (TPC), and total flavonoid contents (TFC). The investigated plants were Anacardium occidentale, Spondiasdulcis, Annona muricata, Euterpe oleracea, Oenocarpus bacaba, Luffa acutangula, Punicagranatum, Malpighia emarginata, Syzygiumaqueum, Syzygiumcumini, Averrhoa carambola, and Renealmiaalpinia (fruit); Hibiscus sabdariffa (calyx); as well as Aloe vera and Cestrum latifolium (leaf). Aqueous extracts (1 - 3,000 μg/ mL) were prepared. AA was determined by the FRAP and the DPPH assay. TPC and TFC were determined by the Folin-Ciocalteu’s and an AlCl3 colorimetric method, respectively, using gallic acid (GA) and rutin (R), respectively, as standards. Data are means ± SDs (n ≥ 3; P < 0.05). FRAP values and DPPH-scavenging activities correlated positively with each other and with TPC but not with TFC. The preparations from M. emarginata, A. carambola, A. occidentale, O. bacaba, C. latifolium, and H. sabdariffa displayed the highest FRAP values (54 ± 14 to 412 ± 30 µM Fe2+/100 μg), DPPH-scavenging activities (IC50 values of 33 ± 14 to 250 ± 50 μg/mL), and TPC (51 ± 4 to 280 ± 78 µM GAE/100 µg). TFC of all samples were ≤ 10 ± 3 RE/100 µg. The adaptogenic properties of these plants may (partially) be attributed to their high content of antioxidant phenolic compounds and may make them candidates of novel sources of health-promoting antioxidants.
Keywords: Suriname; medicinal plants; adaptogenic properties; antioxidant activity; total phenolic content; total